THE IMPACT OF LIFESTYLE, ART COLLECTION, AND HEDONIC LIVING ON VISIT INTENTION, VISIT DECISION AND REVISIT INTENTION AT THE NATIONAL GALLERY - Amirah Salwa Mukarommah; Meylani Tuti (Journal of Management Small and Medium Enterprises (SME's), 2023)
The National Gallery hosts several local and foreign travelers for art exhibitions and events. It is intriguing to look at the lifestyle characteristics, gallery art collections, and hedonic factors that affect tourists' decisions to visit the National Gallery. The purpose of this study was to determine the impact of Lifestyle, Art Collection, and Hedonic Living on Visit Intention, Visit Decision, and Revisit Intention in the National Gallery. Purposive sampling was used to collect data on 152 National Gallery visitors in December 2022 for this study. The analytical method employed is the Structural Equation Model, which is supported by SmartPLS software. The results demonstrate that the Hedonic influences the Visit Intention, Visit Decision, and Revisit Intention.  Contrarily, the Visit Intention, Visit Decision, and Revisit Intention are unaffected by Lifestyle. The Art Collection affects Visit Intention and Revisit Intention but has no impact on Visit Decision. Finally, the Visit Decision is influenced by the Visit Intention, which in turn is influenced by the Revisit Intention.